An Energy-Efficient Routing Protocol Via Angle-Based Flooding Zone in Underwater Wireless Sensor Networks - M. Kashif Manzoor; Rana M. Amir Latif; Izharul Haq; N. Z. Jhanjhi (International Journal of Intelligent Systems and Applications in Engineering, 2022)
The underwater wireless sensor network provides a comprehensive range of marine applications considering several aspects, including node float mobility, high error probability, high latency, low bandwidth, and 3-dimensional space. These aspects provide many demanding situations to the network protocol layout. One of the significant challenges the sensor nodes face in routing is energy consumption which reduces the nodes’ lifetime while delivering the packet. Most nodes are battery-powered in an underwater network, so energy efficiency is essential because recharging the node is difficult. Building an energy-efficient, robust network and analyzing energy consumption characteristics is essential because the acoustic signal is affected by many ambient environmental conditions like a high probability of error in transmissions, extensive propagation delays, and volatile network dynamics. We would use a position-based routing approach to conserve sensor nodes’ energy in the UWSN environment. Only a selected area from source to target will forward the packet. In a location-based routing protocol, the location of the sink and its own is known by sensor nodes. So, we can save energy, processing, and time if we find a relay node in a small area. In this way, an optimal relay node would be selected. We will find that area with the angle between sources and sink nodes. So, the flooding zone would be optimal for finding a relay node. If the relay node is in a flooding zone, it will reduce energy, processing, and time, increasing their performance. By using this technique, less, several nodes will participate in routing. To reduce energy consumption, low-benefit packets will be discarded. Moreover, to forward the data packets flooding zone, an angle will be introduced between the surface sink and the source node. With the simulation results, we will prove that the metric parameters such as energy consumption, throughput, transmission, delay, and packet delivery ratio show performance improvement.